2017
DOI: 10.1590/s1980-220x2016034403210
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' knowledge and practices regarding pain management in newborns

Abstract: Objective:To analyze nurses' knowledge and practices regarding pain management of newborns admitted to Neonatal Intensive Care Units. Method: A descriptive and crosssectional study. Data were collected from 51 nurses based on an adapted questionnaire aimed at evaluating knowledge and practices regarding the management of neonatal pain in six hospitals in Curitiba and its Metropolitan Region. Results: For most nurses (86.0%), neonates feel pain. A total of 34.7% of the nurses reported never using pain assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
2
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(117 citation statements)
references
References 21 publications
6
86
2
23
Order By: Relevance
“…This finding correlates with other studies, [21,22] which indicated that nurses had poor knowledge of neonatal pain management. In contrast, other studies, [7,12,16,17] reflected higher scores.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations
“…This finding correlates with other studies, [21,22] which indicated that nurses had poor knowledge of neonatal pain management. In contrast, other studies, [7,12,16,17] reflected higher scores.…”
Section: Discussioncontrasting
confidence: 75%
“…A study in Iran found similar results, [21] whereby pharmacological interventions were rarely used, or never used. [17,21] These findings contrast with the use of non-pharmacological interventions which participants reported as always used. These findings seem understandable given that the use of comfort measures is a fundamental role of nurses.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Essas manifestações podem ser de difícil identificação e avaliação, por isso é fundamental a observação criteriosa e individualizada e a utilização de escalas que possam auxiliar a dimensionar a dor. [2][3] No entanto, no cotidiano da prática assistencial ao recém-nascido observam-se dificuldades dos profissionais de saúde relacionadas a avaliação e tratamento da dor neonatal.…”
unclassified